Off-ramps and on-ramps : keeping talented women on the road to success - Hewlett, Sylvia Ann, 1946- (Boston, Mass. : Harvard Business School Press, 2007)
Examines the impact that a leave to care for children or elderly parents has on the career of professional women and proposes strategies that companies can undertake to retain and reintegrate talented female employees.
Foreword / by Carolyn Buck Luce -- The challenge -- Why mess with the male competitive model? -- Women's non-linear careers -- Extreme jobs, extreme demands -- The business case for diversity -- Models at the cutting edge -- Establishing flexible work arrangements -- Ernst & Young -- BT Group -- Citigroup -- Creating arc-of-career flexibility -- Booz Allen Hamilton -- Lehman Brothers -- Goldman Sachs -- Reimagining work life -- Citigroup -- Time Warner -- Johnson & Johnson -- Claiming and sustaining ambition -- Johnson & Johnson -- Time Warner -- General Electric -- Tapping into altruism -- Goldman Sachs -- Cisco Systems -- American Express -- Combating stigma and stereotypes -- Lehman Brothers -- Cisco Systems -- Ernst & Young -- Canaries in the coal mine.
Includes bibliographical references (pages 263-277) and index.
Description based on print version record.
Keywords: Women in the professions -- United States; Women -- Employment -- United States; Corporations -- United States -- Case studies; Working mothers -- United States; Work and family -- United States; Femmes dans les professions libérales -- États-Unis.; Femmes -- Travail -- États-Unis.; Entreprises -- États-Unis -- Cas, Études de; Mères au travail -- États-Unis.; Travail et famille -- États-Unis.; Corporations -- United States -- Case studies; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books